Condition Numbers of the Nonlinear Matrix Equation Xp-A⁎eXA=I - Chacha Stephen Chacha; Syed Muhammad Raza Shah Naqvi (Journal of Function Spaces)
We explore the condition numbers of the nonlinear matrix equation Xp-A⁎eXA=I. Explicit expressions for the normwise, mixed, and componentwise condition numbers are derived. The upper bounds for the mixed and componentwise condition numbers are obtained. The numerical result favors the fact that our estimations are fairly sharp. Also, the relative upper perturbation bounds give satisfactory results for small perturbations in the input data.